Storytelling Branding as a Moderator of Personal Branding on Personal Image: Evidence from YouTube Content Creators - Mohamad Hadi Prasetyo (Politeknik Siber Cerdika Internasional, 2026)
Background: YouTube has transformed content creators into personal brands competing to establish credible and distinctive images. However, the effectiveness of personal branding may depend on how creators communicate their identities through storytelling. Objective: This study analyzes the moderating role of storytelling branding in the relationship between personal branding and the personal image of YouTube content creators. Methods: This quantitative explanatory study surveyed 256 Indonesian YouTube users selected through purposive sampling. Data were collected using an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. Results: Personal branding significantly and positively influenced personal image (β = 0.533; t = 7.987; p < 0.001). Storytelling branding also had a significant positive effect on personal image (β = 0.342; t = 4.905; p < 0.001). Furthermore, storytelling branding significantly strengthened the relationship between personal branding and personal image (β = 0.114; t = 2.207; p = 0.027). Conclusion: Consistent personal branding enhances content creators’ personal images, while authentic, emotionally engaging, and coherent storytelling strengthens this effect. YouTube content creators should therefore integrate strategic storytelling into their personal branding practices.